Subungual Keratoacanthoma: A Rare Variant of Keratoacanthoma - Alexandre Miroux Catarino; Maria Goreti Catorze; Isabel Viana (Sociedade Portuguesa de Dermatologia e Venereologia, 2018)
Sungungual keratoacanthoma is a rare and more aggressive variant of keratoacanthoma. The authors present a case of a 49-year-old male with a one year history of a growing exophytic nodule on the nail bed of the left first toe. Physical examination revealed a two centimeters large exofitic nodule with a verrucous hyperkeratotic central area on the nail bed. A plain radiograph showed a cup-shaped lytic defect in the underlying distal phalanx. Histopathologic analysis revealed a large crater-like squamoproliferative lesion, connected to the epidermis and consisting of lobules and nests of glassy epithelium with numerous dyskeratotic cells, very little degree of cytological atypia and low mitotic activity. Lymphovascular, perineural or bone invasion were not found. Immunohistochemistry with p53 and Ki67 showed exclusive focal basal staining. The diagnosis of subungual keratoacanthoma was made. The main differential diagnosis, both clinical and histological, is with squamous cell carcinoma. It is important to consider this entity to avoid unnecessary diagnostic delays and mutilating treatments.